INVENTARISASI TANAMAN BAMBU YANG TERDAPAT DI BALAI KEBUN RAYA BATURRADEN BANYUMAS JAWA TENGAH - Melisa Oktaviani Sukma; Lianah Lianah (Fakultas Sains dan Teknologi, UIN Walisongo Semarang, 2019)
Baturraden Botanical Garden (KRB) is a conservation area both ex-situ and in-situ of various plants in the Slamet Mountain area. KRB plays a role in saving various types of plants, one of which is the type of bamboo in the area is rarely updated data. This study aims to inventory which is used in evaluating data on the number and types of bamboo that are in the KRB collection. The study uses descriptive qualitative methods which include exploration, morphological observation, and measurement of environmental factors. Based on field data collection, 40 bamboo specimens were obtained in 17 species, of which there were 7 specimens from 5 species that have not been identified while 33 other specimens belong to 12 different species and 8 genera. The eight clans are Bambusa, Cephalostachyu, Chimonobambus, Dinochloa, Gigantochloa, Melocanna, Schizostachyum, and Semiarundinaria. Schizostachyum caudatum Backer ex K. Hene, Melocanna baccifera (Roxb.) Kurz, Bambusa multiplex (Lour.) Raeusch. ex Schult. is the most commonly found bamboo. Morphological observations included roots, reeds, leaves and midribs. Environmental factors of the Baturraden Botanical Gardens in VAK III.B.I and VAK III.B.II meet the requirements for the growth and propagation of bamboo collections.